Application of Resonant Nuclear Reactions for Studying the Diffusion of Nitrogen and Silicon in Ti-Modified Stainless Steel - J. Arunkumar; C. David; K. G. M. Nair; B. K. Panigrahi; C. S. Sundar (Advances in Materials Science and Engineering)
Resonant nuclear reaction analysis can be used for the study of diffusion behaviour of minor alloying elements in reactor structural materials. In the present paper, 15N(p,αγ)12C and 30Si(p,γ)31P reactions have been used to profile the ion-implanted 15N and 30Si in D9 alloy (titanium-modified austenitic stainless steel). The diffusion coefficients at various temperatures have been estimated from the broadening of the implantation profiles during thermal annealing, and the activation energies are deduced.